2010
DOI: 10.1126/scitranslmed.3000448
|View full text |Cite
|
Sign up to set email alerts
|

The Inducible Costimulator (ICOS) Is Critical for the Development of Human T H 17 Cells

Abstract: Human T helper 17 (TH17) cells regulate host defense, autoimmunity, and tumor immunity. Although cytokines that control human TH17 cell development have been identified, the costimulatory molecules important for TH17 cell generation are unknown. Here, we found that the inducible costimulator (ICOS) was critical for the differentiation and expansion of human TH17 cells. Human cord blood contained a subset of CD161+CD4+T cells that were recent emigrants from the thymus, expressed ICOS constitutively, and were im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
217
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(232 citation statements)
references
References 51 publications
14
217
1
Order By: Relevance
“…Moreover, we found that B7h triggering in human DCs increases the secretion of IL-23 (which is involved in Th17 expansion and survival) and supports Th17 cell activity (18). Finally, ICOS triggering in T cells (which is blocked by ICOS-Fc) is involved in the differentiation of both Tregs and Th17 cells (17,(31)(32)(33); however, its support of Treg differentiation prevails in the tumor environment (34,35).…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, we found that B7h triggering in human DCs increases the secretion of IL-23 (which is involved in Th17 expansion and survival) and supports Th17 cell activity (18). Finally, ICOS triggering in T cells (which is blocked by ICOS-Fc) is involved in the differentiation of both Tregs and Th17 cells (17,(31)(32)(33); however, its support of Treg differentiation prevails in the tumor environment (34,35).…”
Section: Discussionmentioning
confidence: 96%
“…It is clear that onset of these infDCs resides in inflammatory microenvironments. However, the trigger for DCs to develop into this inflammatory phenotype remains unknown and was not dependent on ICOS/ICOS-L interaction, which is important for Th17 polarization (21,47 DCs]), we observed that iDCs activated with IgG-opsonized E. coli exhibited some expression of inflammatory markers (higher CD14 and CD206 expression, but CD1a, CD14, CD206, and CD11b already were present on E. coli-stimulated DCs; levels of FcεRI and CD209 on infDCs could not be confirmed in our experiments) (Supplemental Fig. 1D).…”
Section: Discussionmentioning
confidence: 99%
“…Malt1 -/-mice were originally generated in our laboratory (20,37) and backcrossed for more than 10 generations into the C57BL/6 backIn vitro, IL-6, IL-21, and IL-23 -with or without TGF-β -have been reported to induce Th17 cell differentiation or stabilization (5,11,12,44,45). However, the roles of TCR stimulation and costimulatory signaling in the differentiation of specific Th subsets have yet to be clearly delineated (46)(47)(48)(49). Engagement of both the TCR and CD28 results in activation of the IKK complex, which relieves NF-κB from its suppression by the IκB proteins.…”
Section: Methodsmentioning
confidence: 99%